Implementasi Sembilan Elemen Jurnalisme Dari Bill Kovach Dan Tom Rosenstiel Dalam Drama Korea Argon Episode 6 Dan 7 (Analisis Pendekatan Semiotika John Fiske) - Aisyah Safitri; Sumaina Duku; Jufrizal (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This Korean drama titled "Argon" is a Korean drama that tells the story of a journalist and reporter named Kim Baek Jin, the leader of an investigative program called Argon. He just wants himself and the Argon team to report the truth. The focus of the research is how the Argon team in episodes 6 and 7 resolved the Sumyoung Food company case. The problems to be studied are how the implementation of the nine elements of journalism contained in episodes 6 and 7 with John Fiske's semiotic analysis and how the professionalism of journalists in the Korean drama Argon episodes 6 and 7 through the level of reality, the level of representation and the level of ideology. The type of this research is descriptive qualitative. Data collection techniques were carried out by documentation, namely collecting scenes in Korean drama Argon episodes 6 and 7 and literature study, which was obtained by obtaining data through journals, theses, books, and articles. The results of this study are Korean drama Argon episodes 6 and 7 showing the implementation of the nine elements of journalism using John Fiske's semiotic analysis with three levels of coding.